Effects of a program to improve self-esteem in children of 8 to 11 years with specific learning problems - Pequeña Constantino, Juan (2006)
It was a program of self-esteem for childrens of 8 to 11 year old with specific learning disorders. They were 30 participants (15 were in the experimental group and 15 were in the control group). It was used an experimental design pre test and post test with control group. In the comparative analysis it was found that there were significative differences in the area itself (t = - 4.06, p< .01) home (t = -2.26, p < .05) school (t = -3.45, p< .01) mats (t = -3.06, p <.01) and in total self esteem (t = -6.23, p < .001), in all cases the post test was greater than pre test, this results corroborate the efectiveness of the program.